2018
DOI: 10.1007/s40262-018-0649-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety and Tolerability of Oral Semaglutide in Subjects with Renal Impairment

Abstract: BackgroundSemaglutide, a glucagon-like peptide-1 (GLP-1) analogue, has been co-formulated with the absorption enhancer sodium N-(8-[2-hydroxybenzoyl] amino) caprylate (SNAC) as a tablet for oral administration. This trial (NCT02014259) investigated the pharmacokinetics, safety and tolerability of oral semaglutide in subjects with and without renal impairment.MethodsSubjects were categorised as having normal renal function (n = 24), mild (n = 12), moderate (n = 12) or severe (n = 12) renal impairment, or end-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 28 publications
8
86
0
2
Order By: Relevance
“…24 Oral semaglutide is the first oral GLP-1 receptor agonist and, once available, might be preferred to injections by some patients. Like liraglutide and subcutaneous semaglutide, the pharmacokinetics of oral semaglutide are not substantially affected by renal impairment, 11,12,25 making it potentially suitable for patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Oral semaglutide is the first oral GLP-1 receptor agonist and, once available, might be preferred to injections by some patients. Like liraglutide and subcutaneous semaglutide, the pharmacokinetics of oral semaglutide are not substantially affected by renal impairment, 11,12,25 making it potentially suitable for patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In people without diabetes, the pharmacokinetics of oral semaglutide were not affected by renal impairment. 12 However, the efficacy and safety profile of oral semaglutide in patients with diabetes and renal impairment is unknown. In this phase 3a trial (PIONEER 5), we compared the efficacy and safety of once-daily oral semaglutide with placebo, in addition to existing background medication, in patients with type 2 diabetes and moderate renal impairment (eGFR of 30-59 mL/min per 1•73 m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pharmacodynamics, pharmacokinetics, and safety of once‐weekly sc semaglutide were similar between Caucasian and Japanese healthy individuals as shown in a randomized trial . Pharmacokinetics, safety, and tolerability of oral semaglutide have been found not to be altered in patients with various degrees of renal or hepatic impairment, thus suggesting that no dose adjustments are needed for oral semaglutide in relation to renal or hepatic function …”
Section: Chemical Structure and Pharmacokinetics Of Semaglutidementioning
confidence: 66%
“…Another meta‐analysis showed that semaglutide‐treated patients were less likely to develop nausea compared with the other GLP‐1 RAs . In terms of pharmacokinetics, no semaglutide dose adjustments are required in patients with renal or liver dysfunction or in patients receiving warfarin, digoxin, atorvastatin, or metformin …”
Section: Safety Of Semaglutidementioning
confidence: 99%
“…The company expects to launch this oral formulation before mid 2019. 84,85 The Dermal Route Does the dermal route offer opportunities to deliver biologics for systemic use? Up until now, all attempts of transporting therapeutically relevant doses of proteins through the intact skin by using patch-type devices have failed.…”
Section: Routes and Techniques Of Administration The Oral Routementioning
confidence: 99%